1993
DOI: 10.1227/00006123-199308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Endoneurosurgical Therapy for Aqueductal Stenosis

Abstract: We successfully managed 11 patients with aqueductal stenosis of adult or adolescent onset, with no mortality or significant morbidity, by using a flexible ventriculoscope to perform either a third ventriculostomy or an aqueductal plasty. A flexible fiberoptic ventriculoscope and its accessories were newly developed, and surgical techniques were improved. For all patients, cinemagnetic resonance imaging was a critical part of the preoperative and postoperative evaluation of cerebrospinal fluid flow in the third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…ETV has been reported to be effective in the treatment of hydrocephalus with success rates ranging between 49 and 100%, depending on the aetiology of hydrocephalus, the criteria used for patient selection, and the follow-up period [2, 3, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Despite these encouraging reports, most authors have suggested that the outcome following ETV is significantly worse in children less than 1 year old as compared with older children [4, 10, 16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…ETV has been reported to be effective in the treatment of hydrocephalus with success rates ranging between 49 and 100%, depending on the aetiology of hydrocephalus, the criteria used for patient selection, and the follow-up period [2, 3, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. Despite these encouraging reports, most authors have suggested that the outcome following ETV is significantly worse in children less than 1 year old as compared with older children [4, 10, 16, 17, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of shunt-free treatment of hydrocephalus are obvious. In the last decade, various articles dealing with the advantages of endoscopic 3rd ventriculostomy have been published [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. In addition, some reports of successful 3rd ventriculostomy in communicating or unclear hydrocephalus exist [12, 13, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…These range from type (rigid or flexible) and brand of the neuroendoscope used to the various tools used to open and dilate the floor of the third ventricle [3, 4, 5, 6, 14, 15, 16, 17, 18, 19]. In general, there are several ways to perform the procedure, and to a large part surgeon preference dominates the decision tree.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of the initial opening of the third ventricular floor include the utilization of gentle blunt passage of the neuroendoscope or the use of an electrocautery wire or a laser fiber (Yag/Nd or KTP) [4, 15, 16, 17, 18]. Following this initial perforation, dilatation may be accomplished using a 2-Fr Fogarty balloon catheter (Fogarty arterial embolectomy catheter; Baxter Healthcare, Irvine, Calif., USA) [3, 4, 6, 16]. Another well-known method utilizes the passage of a 1.1- to 1.2-mm neuroendoscope through the peel-away introducer sheath [2, 4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation